A new synthetic pathway based on one-pot sequential aza-Michael addition and photoCuAAC click reactions. Issue 9 (7th February 2019) - Yin, Boyang; Croutxé-Barghorn, Céline; Delaite, Christelle; Allonas, Xavier
Abstract : A solvent-free process is described for the synthesis of tailor-made molecules from a one-pot, two-step approach combining aza-Michael addition and photoinduced copper(i ) catalysed azide–alkyne (photo-CuAAC) reactions. Abstract : A solvent-free process is described for the synthesis of tailor-made molecules from a one-pot, two-step approach combining aza-Michael addition and photoinduced copper(i ) catalysed azide–alkyne (photo-CuAAC) reactions. After the first reaction between an amine and an acrylate, cycloaddition between an azide and an alkyne is activated by light irradiation in the presence of a copper complex. The kinetics of the aza-Michael addition and photo-CuAAC reaction were investigated by liquid state 1 H NMR spectroscopy and real-time Fourier transform infrared spectroscopy. This new process represents a well-defined spatio-temporal pathway to the synthesis of bespoke intermediate molecules for various applications.